2020
DOI: 10.1002/adsu.202000092
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Insight into the Structure and Formation of Coke on PtSn Alloy during Propane Dehydrogenation

Abstract: Propane dehydrogenation (PDH) catalyzed by PtSn/Al2O3 is a vital industrial process for producing propylene, a significant building block in the chemical industry. However, coke produced in the process deactivates the catalyst and the energy‐intensive regeneration procedures can produce considerable CO2 emission. In this work, coke on the spent catalysts is analyzed by thermogravimetric‐mass spectra, Raman spectra, 1H solid NMR spectra, and infrared spectra. Several C3 species, including propyl, propylidene an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…The proportion of each kind of coke and species under their reaction condition were given, and the aliphatic cokes take up the larger part of coke deposition, with the ratio of C/H around 1.5. However, a coke hydrogenation study indicated that the species of coke deposition vary on different catalysts . It is suggested that the species could be atomic carbon or aromatics on Pt/Al 2 O 3 and C 3 species on PtSn/Al 2 O 3 catalyst, respectively.…”
Section: The Acquaintance Of Cokementioning
confidence: 99%
See 2 more Smart Citations
“…The proportion of each kind of coke and species under their reaction condition were given, and the aliphatic cokes take up the larger part of coke deposition, with the ratio of C/H around 1.5. However, a coke hydrogenation study indicated that the species of coke deposition vary on different catalysts . It is suggested that the species could be atomic carbon or aromatics on Pt/Al 2 O 3 and C 3 species on PtSn/Al 2 O 3 catalyst, respectively.…”
Section: The Acquaintance Of Cokementioning
confidence: 99%
“…As mentioned in section 2.1, adding promoter is one of the most effective methods to modify the nature of Pt catalyst. Tin is the most widely applied promoter for Pt, which has enhanced improvements in many reports. ,,, The main effect of Sn is to improve the selectivity and stability as shown in entries 1–3 of Table . Moreover, the coke precursor adsorbed weakly on PtSn, which enables the easy transfer from metal to support .…”
Section: Suppression and Elimination Of Coke Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pt-Sn is one of the most promising catalytic systems, the performance of which is strongly dependent on its structure. Sn can promote the separation of multifold Pt sites and donate electrons to Pt; comparative studies between Pt/Al 2 O 3 and PtSn/Al 2 O 3 highlight, in the case of bimetallic catalyst, a significantly higher propylene selectivity and only traces of cracking products [35]. In fact, the multifold Pt (111) sites are more active towards the breaking of C-C bonds than the PtSn (102).…”
Section: Bimetallic and Promoted Catalystsmentioning
confidence: 99%
“…Isolation of Pt atoms is an efficient strategy to inhibit the undesirable side reactions of PDH. Pt–Pt ensembles can be diluted, and propylene selectivity and catalyst stability can be enhanced when alloyed with certain inactive metals such as Sn, Ga, Zn, , In, , Cu, , Ni, and Ge. , These bimetallic catalysts have been studied to improve catalytic performance, among which Pt–Sn catalyst is the most classic example.…”
Section: Introductionmentioning
confidence: 99%